Unveiling the driving role of pH on community stability and function during lignocellulose degradation in paddy soil - Wang, Yi; Chen, Yonglun; Gao, Xiuqing; Wang, Qiong; Cui, Mingyu; Zhang, Dongdong; Guo, Peng (Frontiers in Microbiology, 2024)
Introduction Crop straw, a major by-product of agricultural production, is pivotal in maintaining soil health and preserving the ecological environment. While straw incorporation is widely recognized as a sustainable practice, the incomplete decomposition of crop residues poses challenges to plant growth, increasing the risk of pests and diseases. This necessitates a comprehensive investigation. Methods The current study employs a 28-day pot experiment to simulate the degradation of rice straw in paddy soils. The impacts of bioaugmentation and biostimulation on lignocellulose degradation are systematically evaluated. Results Results indicate a high lignocellulose degradation ability in paddy soil, with over 80% straw weight loss within 28 days. Bioaugmentation with a lignocellulolytic microbial consortium enhances straw degradation during the initial stage (0–14 days). In contrast, biostimulation with readily available nutrients leads to soil acidification, hindering straw degradation and reducing microbial diversity. Furthermore, pH emerges as a critical factor influencing microbial community stability and function during lignocellulose degradation. Microbial co-occurrence network analysis reveals that microorganisms occupy ecological niches associated with different cellulose components. Notably, Module M2, comprising Proteobacteria, Firmicutes, Gemmatimonadota, Actinobacteriota, Bacteroidota, Myxococcota, Halobacterota, and Acidobacteriota, positively correlates with pH and weight loss. Discussion This study significantly advances our understanding of microbial mechanisms in soil decomposition, emphasizing the pivotal role of pH in community stability and function in paddy soil. These findings can inform future strategies for managing rice straw while safeguarding soil ecosystem health.